(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
A subtype of eosinophilic chronic rhinosinusitis (CRS), allergic fungal sinusitis (AFS) is distinguished by type I hypersensitivity, nasal polyposis, eosinophilic mucus, characteristic computed tomography scan findings, and the presence of fungus on surgical specimens without tissue invasion. Given the relatively early age of onset and the challenge of controlling AFS with commercially available treatment regimens, this refractory subtype of CRS is of particular relevance to the pediatric community. AFS diagnosis almost always necessitates surgical surgery. One of the cornerstones of the pediatric AFS treatment paradigm is postoperative adjuvant medicinal therapy.